Different Levels of Social Media Use on Online Political Participation - Intyaswati, Drina; Venus, Anter; Kusumajanti; Saputra, Windhi Tia; Qasim Mahmood (Jurnal Komunikasi, 2024)
In many studies, social media use related to political information impacts political participation. However, only some have seen how different levels of social media use affect online political participation. This study aims to see how different levels of social media use affect online political participation by using the theory of source credibility. This study was conducted using a survey method by distributing questionnaires through social media networks. The population is Jakarta residents. Using purposive sampling, we obtained a sample of 500 respondents. Results showed that in the low category, apart from gender and education, the use of social media also impacts online political participation. In the medium category, besides the use of social media, gender, education, age, and political trust affect online political participation. In the high category, what influences online political participation are the use of social media, political trust, and social media credibility. The source credibility theory is confirmed only among high users.